Analisis Penggunaan Alat Peraga sebagai Media dalam Meningkatkan Hasil Belajar IPA - Ahmad Mudhoffar Ma’sum (Edudikara: Jurnal Pendidikan dan Pembelajaran, 2023)
the use of an inappropriate learning model will have an impact on the learning process resulting in ineffective learning, students, students become bored and do not focus on the material presented. With this, it triggers researchers to conduct this study in order to determine the effect of using teaching aids as a medium in improving social studies learning outcomes at MI Al-Hamidi cangkring jenggawah. Using the class action assessment method (CAR), which consists of one cycle with four stages, namely: 1) planning 2) implementation 3) observation) reflection. The results of the first test showed that the students’ level of completeness was still low as indicated by the test results of 17 students who completed only 4 children (23.5%) while 13 children (76.4%) had not yet completed. In the second test, there were 17 students who had completed a significant increase in 12 children (70.5%) and 5 students who had not completed (29, 4). This indicates that the use of teaching aids has an effect on improving learning outcomes.